'A vehicle of symbols and nothing more'. George Romanes, theory of mind, information, and Samuel Butler. Issue 3 (September 2015) - Forsdyke, Donald R
Today's 'theory of mind' (ToM) concept is rooted in the distinction of nineteenth-century philosopher William Clifford between 'objects' that can be directly perceived and 'ejects', such as the mind of another person, which are inferred from one's subjective knowledge of one's own mind. George Romanes, a founder with Charles Darwin of the discipline of comparative psychology, considered the minds of animals as ejects, an idea that could be generalized to 'society as eject' and, ultimately, 'the world as an eject' – mind in the universe. Yet, Romanes and Clifford only vaguely connected mind with the abstraction we call 'information', which needs 'a vehicle of symbols' – a material transporting medium. However, Samuel Butler was able to address, in informational terms depleted of theological trappings, both organic evolution and mind in the universe. This view harmonizes with insights arising from modern DNA research, the relative immortality of 'selfish' genes, and some startling recent developments in brain research.